Biophysiology of Panaeolus spp. associated with dried dung of domesticated ruminants - Maylem, Excel Rio S.; Dulay, Rich Milton R.; Kalaw, Sofronio P.; Reyes, Renato G. (2011)
Paneolus is a psychoactive mushroom usually found growing on dried dung of domesticated ruminants such as carabao and horse. In our efforts to look for alternative source of bioactive compounds for dung development, we initiated a study on domestication of this wild mushrooms hallucinogenic activity. The baseline information generated in this research is necessary for the development of production technology towards its sustainability. As a prelude to its domestication, we evaluated the nutritional and physical requirements for efficient mycelia growth of Panaeolus sp. and fruiting body performance on different formulated substrates under aseptic condition. Wild strain of Panaeolus sp. was obtained from dried tissue culture protocol for mushroom. Among the different media evaluated, results revealed that potato sucrose gulaman (PSG) was the best culture medium as indicated by vigorously thick mycelia density and shortest incubation period with a mean of 9 days. Moreover, potato sucrose gulaman with pH of 6.5 incubated under sealed and alternating light-dark condition favoured the mycelia growth of Panaeolus sp. Aseptic cultivation using 90% carabao dung and 10% rice bran recorded thick and fast mycelia growth and shortest incubation period with a mean of 11 days. However, 90% horse dung and 10% rice bran yielded more fruiting bodies with a mean of 0.39g, highest mean height of 33.67 mm and highest biological efficiency with a mean of 1.15%.
Keywords: Mushrooms; Varieties; Ruminants